PRILAKU SOSIAL KEAGAMAAN BURUH TANI DI SUNGKAI JAYA LAMPUNG UTARA - Reza Nur Arifa (An Natiq, 2023)
Socio-religious behavior is carrying out religious teachings that are carried out consciously and sincerely which are practiced in the social strata of society. The purpose of this study was to determine the social-religious behavior of farm workers in Sungkai Jaya, North Lampung and the inhibiting factors of farm workers in carrying out social-religious practices in Sungkai Jaya, North Lampung. The method used is the field method (Field Research). Data obtained through the method of observation, interviews and documentation. There were 3 informants with the criteria of having worked for at least 5 years, aged 25-50 years, already married, did not own agricultural land. Data analysis was narrated in a qualitative description through three stages, namely data reduction, data presentation and conclusion. The results of this study indicate that the social behavior of farm workers is very good in terms of mutual cooperation activities, visiting sick people, night patrols, and helping each other which is still being implemented today, but for their own religion it is still less visible than when the time for prayer arrives, farm workers are still being in the fields, for example, when the midday prayer arrives, they use their time to rest, not to worship, just as on Friday, only a few come to perform Friday prayers at the mosque. The inhibiting factors for carrying out socio-religious activities are the low economy of farm laborers which forces them to spend their time working hard in order to make ends meet and the low level of education so that they have no other choice but to work as farm labourers.